1993
DOI: 10.1177/0265407593104006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Jealous Responses: The Influence of Adult Attachment and Depression on Threat Appraisal

Abstract: This study tested a model of romantic jealousy based on cognitive motivational theory (White & Mullen, 1989) and formulations from adult attachment studies (Hazan & Shaver, 1987). A causal model was tested in which attachment, depression and situational threat were hypothesized to predict jealous responses through their effects on appraisal of threat. Imagery scenes, depicting varying levels of threat by a romantic relationship rival, were presented to 135 undergraduates. The model fit the data very we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 21 publications
3
43
0
4
Order By: Relevance
“…The null findings at the actor level are consistent with previous research showing inconsistent findings between attachment anxiety and support-seeking (Alexander, Feeney, Hohaus, & Noller, 2001;Berant, Mikulincer, & Florian, 2001;Ognibene & Collins, 1998;Radecki-Bush, Farrell, & Bush, 1993). Thus, it is possible that anxiously attached individuals do not always seek support when distressed as they worry about the availability of the attachment figure due to a history of receiving unpredictable or inconsistent care and support (Ainsworth et al, 1978;Brenning et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The null findings at the actor level are consistent with previous research showing inconsistent findings between attachment anxiety and support-seeking (Alexander, Feeney, Hohaus, & Noller, 2001;Berant, Mikulincer, & Florian, 2001;Ognibene & Collins, 1998;Radecki-Bush, Farrell, & Bush, 1993). Thus, it is possible that anxiously attached individuals do not always seek support when distressed as they worry about the availability of the attachment figure due to a history of receiving unpredictable or inconsistent care and support (Ainsworth et al, 1978;Brenning et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Several theories of jealousy predict that relationship commitment and the attractiveness of relationship alternatives should interact to facilitate the expression of jealousy because to the extent that individuals are more committed to their relationship and perceive that they have unattractive dating alternatives, a jealousy-evoking situation should be perceived as especially threatening to the self, to the relationship, and to the emotional, temporal, and material investments put into the relationship (e.g., Bringle, 1991;Bush, Bush, & Jennings, 1988;Buunk, 1991;Hansen, 1991;Radjecki-Bush, Farrell, & Bush, 1993;White, 1981White, , 1991White & Mullen, 1989). Although men and women react differently to threat, evolutionary theory predicts that cognitive mechanisms are activated when a romantic relationship is threatened (e.g., Buss, 2000).…”
Section: Studymentioning
confidence: 99%
“…Many studies have shown that differences in attachment style seem to influence patterns of jealousy expression [37][38][39]. Yumbul et al [40] stated individuals with anxious ambivalent attachment styles presented the most jealousy in romantic relationships, followed by those with avoidant and secure ones.…”
Section: Discussionmentioning
confidence: 99%